Estudio de prefactibilidad para brindar el servicio de transporte fluvial de alimentos perecibles en la selva Nor Oriental del Perú - Farfán Zúñiga, Claudia Cira (2016)
This study proposes to launch a river transport service of perishables for oil companies in the northern jungle region , which for ms an important part of thebalanced diet that every worker should have .The main objective is to prov ide a continuous service all year.